Color enhancement of refined-bleached used vegetable oils as dielectric liquid: two-level factorial design approach - Muhammad Syahrani Johal; Sharin Ab Ghani; Imran Sutan Chairul; Mohd Shahril Ahmad Khiar; Muhamad Falihan Bahari (Institute of Advanced Engineering and Science, 2023)
Number of findings have shown that the used vegetable oils (UVOs) properties can be enhanced by changing their chemical structure and can be utilized as dielectric liquid in oil-immersed transformers. However, earlier researchers used the one-factor-at-a-time (OFAT) method for their experimental design approach. Nevertheless, they failed to consider the possibility that combining the mixing process parameters at the highest ratios could produce a more favorable outcome. Hence, in this study, two-level (2k) factorial design is applied to achieve the highest color reduction of UVOs through chemical refining process known as refined-bleached UVOs (RBUVOs). The involved process parameters are oil temperature, mixing speed and mixing time. Based on the results of 23 factorial design, it is found that mixing time and oil temperature has the most significant effects on color reduction, with a percentage contribution of 35.00% and 32.51%, respectively. The result also shows that the best mixing process parameters of RBUVOs were oil temperature (80 °C), mixing speed (1,000 rpm) and mixing time (60 min). These resulted in the highest color reduction of RBUVOs by 79.27%.